SPP Payment Recording Information System and SMS Gateway Using the Waterfall Method - Muhamad Zaqy; Galih Galih; Moch Irwan Hermanto (Media Jurnal Informatika, 2025)
The utilization of information and communication technology in the field of education has not been maximized, one of which is the management of tuition payment data at SMK Bhakti Putra, which still uses conventional methods and has not been computerized. Based on the above problems, this study aims to design and develop a web-based information system and use SMS Gateway that can help manage tuition payment data. The data collection method in this study is the observation method by directly observing the work processes carried out in the agency to obtain a clear picture of the object being studied. The results of this study are a web-based tuition payment information system and SMS Gateway developed using PHP, MySQL, and the Bootstrap Framework. The result is a new system that can maximize the work of the TU (Administration) section in presenting payment information, accuracy, and administrative services for tuition payments can be carried out effectively and efficiently,as proven by a score of 67.5 which is a marginal result, which is acceptable and needs to be improved, after an evaluation using the SUS method.